DNA methylation changes and improved sleep quality in adults with obstructive sleep apnea and diabetes. Issue 1 (15th November 2019) - Bigini, Evelyn G; Chasens, Eileen R; Conley, Yvette P; Imes, Christopher C
Abstract : Objective: Obstructive sleep apnea (OSA) is common among adults with diabetes. However, little is known about the impact of OSA treatment on DNA methylation levels. The purpose of this study is to explore changes in DNA methylation levels among adults with these conditions enrolled in a randomized controlled trial. Research design and methods: Participants were randomized to continuous positive airway pressure (CPAP) treatment or sham-CPAP placebo for 12 weeks. All participants received diabetes education and counseling. At baseline and 12 weeks, white blood cell DNA methylation levels for five candidate genes ( ANGPTL4, DAPK3, KAT5, PER1, and TNFAIP3 ) and hemoglobin A1C (A1C) levels were obtained from blood. The Pittsburgh Sleep Quality Index (PSQI) and the Epworth Sleepiness Scale (ESS) assessed sleep quality and daytime sleepiness, respectively. T-tests examined within-subject changes from baseline to 12 weeks. Regression analyses explored associations between DNA methylation changes and baseline variables, minutes of therapeutic CPAP use, and changes in A1C levels, PSQI scores, and ESS scores. Results: Participants (n=10) were 70% female, 80% white, and 61.7±7.9 years old. Among all participants from baseline and 12 weeks, TNFAIP3 and PER1 DNA methylation levels decreased. At baseline, PER1 methylation levels were significantly higher in males and sex-based difference in methylation level changes was observed from baseline to 12 weeks. Changes in DNA methylation levels were not associated with minutes of therapeutic CPAP use or changes in A1C, PSQI scores, and ESS scores. Conclusions: While DNA methylation level changes were observed in the study, the causal mechanism is unclear and additional work is needed. Although the methylation changes were small, the long-term effects are unknown.